2012
DOI: 10.1093/infdis/jis590
|View full text |Cite
|
Sign up to set email alerts
|

Fall in Human Papillomavirus Prevalence Following a National Vaccination Program

Abstract: Four years after the commencement of the Australian HPV vaccination program, a substantial decrease in vaccine-targeted genotypes is evident and should, in time, translate into reductions in HPV-related lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
155
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(173 citation statements)
references
References 20 publications
13
155
0
5
Order By: Relevance
“…12 The quadrivalent HPV (6/11/16/18) virus-like particle (qHPV) vaccine is highly efficacious in preventing infection and cervical, vaginal, vulvar, and anal dysplasia caused by HPV 6/11/16/18 as well as HPV 6/11-related condyloma, [13][14][15][16] and the bivalent HPV (16/18) vaccine is highly efficacious against HPV 16/18-related infection and cervical dysplasia. 17 Postlicensure studies have shown a rapid decrease in the incidence of high-grade cervical abnormalities, [18][19][20][21] prevalence of vaccine HPV types, [22][23][24][25][26] and incidence of genital warts [27][28][29][30][31] in vaccinees. Data have shown that prophylactic HPV vaccination is generally safe and well tolerated.…”
Section: What This Study Addsmentioning
confidence: 99%
“…12 The quadrivalent HPV (6/11/16/18) virus-like particle (qHPV) vaccine is highly efficacious in preventing infection and cervical, vaginal, vulvar, and anal dysplasia caused by HPV 6/11/16/18 as well as HPV 6/11-related condyloma, [13][14][15][16] and the bivalent HPV (16/18) vaccine is highly efficacious against HPV 16/18-related infection and cervical dysplasia. 17 Postlicensure studies have shown a rapid decrease in the incidence of high-grade cervical abnormalities, [18][19][20][21] prevalence of vaccine HPV types, [22][23][24][25][26] and incidence of genital warts [27][28][29][30][31] in vaccinees. Data have shown that prophylactic HPV vaccination is generally safe and well tolerated.…”
Section: What This Study Addsmentioning
confidence: 99%
“…24 Our observed safety findings are also similar to that of other studies, whereby vaccine recipients have higher rates of injection site pain, erythema and swelling, but similar rates of systemic AEs. 32 Given the high vaccine efficacy seen in the clinical trials, and the fact that in the 8 y since its original licensure, the qHPV vaccine has been shown to be highly effective at the population level, with marked reductions in the prevalence of HPV vaccine-type related infection and disease in many countries, [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] our findings suggest the vaccine should be equally effective in sub-Saharan African women.…”
mentioning
confidence: 99%
“…Similarly, within the Canadian context, the HPV Focal trial in British Columbia showed that primary hpv testing starting at age 25 resulted in high rates of hpv positivity and cytologic abnormalities requiring followup in women less than 30 years of age 18 . As the vaccinated cohort of women starts screening, hpv positivity rates and cytologic abnormalities will decline 27,28 , making a delay in screening more acceptable.…”
Section: Discussionmentioning
confidence: 99%